On the change of the German financial system - Reinhard H. Schmidt (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
The financial crisis of 2007-08 has stressed the importance of a sound financial system. Unlike other studies weighing the pros and cons of market versus bank-based systems, this paper investigates whether the main elements of the German financial system can be regarded as complementary and consistent. This assessment refers to the idea that there is a potential for positive interaction between different elements in the system that is actually used to make it more valuable to economy and society and more robust to crises. It is shown that the old German bank-based system, where the risk of long-term lending by large private commercial banks was limited by the membership in supervisory boards and strong personal ties between all stakeholders, was a consistent system of well-adjusted complementary elements. After reunification, a hybrid system has emerged where, on the one hand, public savings banks and cooperative banks maintain their role as lenders, but on the other, large private banks have withdrawn from their former dominant role in financing and corporate governance. It is argued that this transition to stronger capital-market and, accordingly, shareholder value orientations has occurred at the expense of consistency.
urn:nbn:de:hebis:30:3-507387
Keywords: 330; German financial system; corporate governance; German banks